Transcriptome analysis of Pseudomonas syringae pv. tomato DAPP-PG 215 in response to silver nanoparticles exposure - Orfei, Benedetta; Pothier, Joël F.; Scotti, Luca; Aceto, Antonio; Moretti, Chiaraluce; Buonaurio, Roberto; Smits, Theo H. M. (Frontiers in Microbiology, 2026)
Silver nanoparticles (AgNPs) are one of the most promising options for the control of bacterial pathogens. The effectiveness of AgNPs has been proven by several recent research studies in which toxicity against a broad range of human and plant pathogenic bacteria was observed, even when used at low doses compared to other conventional bactericides. Nevertheless, the antibacterial mechanism of AgNPs is yet to be completely understood. This study investigated the first response of Pseudomonas syringae pv. tomato strain DAPP-PG 215, the causative agent of bacterial speck disease of tomato, to AgNPs. Gene expression of P. syringae pv. tomato in response to AgNPs was observed after 10 and 30 min of exposure. A total of 78 and 66 genes were identified as differentially expressed, respectively. Gene ontology and KEGG pathway enrichment analysis revealed a high representation of genes related to stress resistance, energy metabolism, and metal ion binding proteins, with different transporters involved. Validation of four selected genes by quantitative RT-PCR analysis, confirmed these observations. These results not only supported initial findings on the antimicrobial action of AgNPs but also suggested a significant impact of different heavy metal and toxin transporters in the silver detoxification mechanism of bacteria.